Handbook of agriculture : facts and figures for farmers, students, and all interested in farming. (New Delhi : Directorate of Information and Publications of Agriculture, Indian Council of Agricultural Research, 2009)
Contributed articles; with reference to India.
Previously published: 5th ed. 2006.
Keywords: Agriculture